Kejahatan Politik Dalam Pembangunan Dalam Kebijakan Pembangunan Industri Kehutanan dan Perkebunan Di Provinsi Riau: Universitas Islam Riau - Sobri Sobri (UIR PRESS, 2019)
State development policies since the New Order era oriented towards rapid economic growth (capitalist paradigm) in an effort to increase the country's foreign exchange as development capital through the development program of indusrialisasi the plantation and forestry sector in Indonesia, especially in Riau province, has led to the widespread conversion of land functions and the occurrence of practices monopoly over natural resources by corporations. In line with the increasingly widespread industrial estate of oil palm plantations and industrial plantations in Riau Province development policies take place unfairly for the local communities, these policies have weakened traditional community access to access to natural resources , loss of natural economic resources of traditional communities (subsistence) and the occurrence of marginal situations socially, economically and culturally, for traditional communities who live in the villages in the province of Riau The manifestation of social, economic, cultural injustice and the process of marginalization, seizure of customary communal land, widespread structural poverty in the villages where local residents reside in Riau Province indicate that the policy of industrialization development in the plantation and forestry sector in Riau province contains dimensic violence and crime.